Covid-19: Portrait of Preservation of the Batik Industry as a Regional Autonomy - Noburu, Itoimiham; Himki, Arzo; Dithi, Arusyi; Kano, Katoyusyi; Anggraeni, Mey (Aptisi Transactions On Technopreneurship (ATT), 2020)
In 2020 coronavirus (covid-19) has shocked the world. This virus attacks the immunity of a person's body and the spread of this virus is very fast. The weakening of the Chinese economy due to the co-19 epidemic certainly had a significant impact on the world, because China is a country that is very influential in the world economy. Many various countries were affected by co-19, including Indonesia. This co-19 outbreak is one of the causes of the decline in people's economic capacity. Many companies suffered losses due to the impact of the covid-19 outbreak, the impact experienced one of them in the field of creative industries, many industries had to close because they were affected by the covid-19. One example of industries that are affected by covid-19 is the batik industry typical of Sumenep. In addition to industry, the tourism sector was affected, many tourist sites were closed due to the co-19 impact which did not allow the public to gather in many crowds. The government has made several efforts to reduce the spread of this epidemic by implementing Large-Scale Social Restrictions or commonly called PSBB in almost all areas according to government regulations. The research method used in this study is to use a qualitative perspective method where this research was conducted with the aim of developing and improving Sumenep batik craftsmen during the covid-19 pandemic. The government has made several efforts to reduce the spread of this epidemic by implementing Large-Scale Social Restrictions or commonly called PSBB in almost all areas according to government regulations. The research method used in this study is to use a qualitative perspective method where this research was conducted with the aim of developing and improving Sumenep batik craftsmen during the covid-19 pandemic. The government has made several efforts to reduce the spread of this epidemic by implementing Large-Scale Social Restrictions or commonly called PSBB in almost all areas according to government regulations. The research method used in this study is to use a qualitative perspective method where this research was conducted with the aim of developing and improving Sumenep batik craftsmen during the covid-19 pandemic.